Factors Related to The Incident of Preeclamsm in Pregnant Women in The Working Area of The Batujaya PUSKESMAS Karawang District - Anna Siauta, Jenny; Dessy Dian Permatasari; Yenny Aulya (Rajaki of Tulip Medika Publisher, 2024)
Background: Pre-eclampsia is the main cause of maternal and fetal death due to hypertension in pregnancy which is typical of pregnancy which is characterized by symptoms of edema, hypertension, and proteinuria that occur after 28 weeks of gestation and the cause is unknown. Objective: To determine the factors related to the incidence of preeclampsia of pregnancy in the Working Area of the Batujaya Health Center, Karawang Regency in 2024. Methods: This study used a case control study design. The study population is mothers who live in the working area of the Batujaya Health Center who conduct antenatal care examinations. The research sample used the total sampling technique and used the inclusion and exclusion criteria, the number of samples was obtained as many as 126 pregnant women with a 1:1 ratio of control cases. Medical records from the Maternal and Child Health (KIA) book and questionnaires. Data analysis using the Chi Square test. Results: The results of this study showed that there was a significant relationship between nutritional status p value=0.017, history of preeclampsia p value=0.001, diabetes p value=0.013, knowledge p value = 0.009 with the incidence of preeclampsia while multiple pregnancies had no relationship with the incidence of preeclampsia p value=1. Conclusion: There is a significant relationship between nutritional status, history of preeclampsia, diabetes, and knowledge with the incidence of preeclampsia while multiple pregnancies are not related to the incidence of preeclampsia in pregnant women in the Working Area of the Batujaya Health Center, Karawang Regency in 2024. Suggestion: Pregnant women need regular ANC examinations so that they can reduce the impact of complications so that if preeclampsia occurs, it can be treated quickly and appropriately.